Video rasterstereography of the spine and pelvis in eight erect positions: A reliability study. Issue 1 (February 2020) - Alzyoud, K.; Hogg, P.; Snaith, B.; Preece, S.; England, A.
Abstract: Introduction: To investigate the reliability and variability of Video Rasterstereography (VR) measurements of the spine and pelvis, for eight proposed standing postures, in order to help define an optimal standing position for erect pelvis radiography. Methods: Surface topography data were collected using the formetic 4D dynamic modelling (Diers) system. 61 healthy participants were recruited; each participant performed eight different standing positions. Four positions were performed with the feet shoulder width apart and parallel, and four positions were performed with the feet shoulder width apart and internally rotated. For the upper extremity, each of the (two sets of) four positions were performed with different arm positions (arms by the sides, arms crossed over the chest, arms 30° flexed and touching the medial end of the clavicle, arms 30° flexed with the hands holding a support). Three sets of surface topography were collected in the eight positions (n = 24). The variability was assessed by calculating standard error of the measurement (SEm) and the coefficient of variation (CV). Reliability was assessed using intra-class correlation coefficients (ICC ± 95% CI). Results: No significant differences in the SEm were found between the three paired measurements for all standing positions (P > 0.05). ICC values demonstrated excellent reliability for all measurements across the eight standing positions (range 0.879–1.00 [95% CI 0.813–1.00]). Conclusion: Evaluating eight standing positions radiographically would be unethical as it would involve repeat radiation exposures. Using the formetic 4D dynamic modelling (Diers) system, provides an alternative and has shown that there was only a minimal, non-statistically significant, differences between the eight different standing positions. Implication for practice: Different standing positions were proposed for erect pelvis radiography.